Clinical outcome of esophageal varices after hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma with major portal vein tumor thrombus - Kodama, Hideaki; Aikata, Hiroshi; Murakami, Eisuke; Miyaki, Daisuke; Nagaoki, Yuko; Hashimoto, Yoshimasa; Azakami, Takahiro; Katamura, Yoshio; Kawaoka, Tomokazu; Takaki, Shintaro; Hiramatsu, Akira; Waki, Koji; et al. (Hepatology research, 2011)
Aim:  To analyze the clinical outcome of esophageal varices (EV) after hepatic arterial infusion chemotherapy (HAIC) in patients with advanced hepatocellular carcinoma (HCC) and major portal vein tumor thrombus (Vp3/4). Methods:  The study subjects were 45 consecutive patients who received HAIC for HCC with Vp3/4 between January 2005 and December 2009. HAIC comprised the combination therapy of intra‐arterial 5‐FU with interferon‐α (5‐FU/IFN) in 23 patients and low‐dose cisplatin plus 5‐FU (FP) in 22. Radiotherapy (RT) was also provided in 19 patients for portal vein tumor thrombosis. Aggravation rate for EV and overall survival rate were analyzed. Results:  The aggravation rates for EV were 47% and 64% at 12 and 24 months, respectively. The survival rates were 47% and 33% at 12 and 24 months, respectively. The response rates to 5‐FU/IFN and FP were 35% and 41%, while the disease control rates in these two groups were 57% and 50%, respectively. There were no significant differences in the objective response and disease control between 5‐FU/IFN and FP. Multivariate analysis identified size of EV (F2/F3) (HR = 7.554, P = 0.006) and HCC disease control (HR = 5.948, P = 0.015) as significant and independent determinants of aggravation of EV, and HCC disease control (HR = 12.233, P < 0.001), metastasis from HCC (HR = 11.469, P = 0.001), ascites (HR = 8.825, P = 0.003) and low serum albumin (HR = 4.953, P = 0.026) as determinants of overall survival. RT for portal vein tumor thrombosis tended to reduce the aggravation rate for EV in patients with these risk factors. Conclusions:  Hepatocellular carcinoma disease control was the most significant and independent factor for aggravation of EV and overall survival in HCC patients with major portal vein tumor thrombosis treated with HAIC.